1996
DOI: 10.1021/jp952854p
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, X-ray Geometry, and Anodic Behavior of Tris[2-(hydroxymethyl)phenyl]phosphane

Abstract: Tris[(monohydroxymethyl)phenyl]phosphanes 5a and 5b were prepared, and the geometry of the ortho-isomer 5a was determined by X-ray diffraction. 5a was found to be propeller-like in shape, exhibiting a helical conformation with the three hydroxymethyl substituents standing on the same side as that with the phosphorus lone pair. Phosphanes 5a and 5b underwent electrochemical one-electron oxidation, giving rise to nonpersistent phosphoniumyl cation radicals 5a ‚+ and 5b ‚+ . The low value of the anodic peak poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In comparison to these alkyl phosphino-triols, our knowledge on related hydroxylated aryl phosphines is still limited; i.e., only a few reports on the two most simple Ph 3 P-based phosphino-triols, namely, P­(C 6 H 4 - o -OH) 3 and P­(C 6 H 4 - o -CH 2 OH) 3 (and their derivatives), have been published to date (see Scheme ). Prior to 2015, several monomeric complexes of P­(C 6 H 4 - o -OH) 3 were known, while the coordination chemistry of P­(C 6 H 4 - o -CH 2 OH) 3 (and its derivatives) was left entirely unexplored. In 2015, Liang and co-workers successfully prepared the sterically shielded hexakis- tert -butyl-substituted derivative of P­(C 6 H 4 - o -OH) 3 (see Scheme ) and its trianion, which marks a milestone in this field, given that several phosphino triphenolate complexes and cluster compounds have been prepared thereafter .…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to these alkyl phosphino-triols, our knowledge on related hydroxylated aryl phosphines is still limited; i.e., only a few reports on the two most simple Ph 3 P-based phosphino-triols, namely, P­(C 6 H 4 - o -OH) 3 and P­(C 6 H 4 - o -CH 2 OH) 3 (and their derivatives), have been published to date (see Scheme ). Prior to 2015, several monomeric complexes of P­(C 6 H 4 - o -OH) 3 were known, while the coordination chemistry of P­(C 6 H 4 - o -CH 2 OH) 3 (and its derivatives) was left entirely unexplored. In 2015, Liang and co-workers successfully prepared the sterically shielded hexakis- tert -butyl-substituted derivative of P­(C 6 H 4 - o -OH) 3 (see Scheme ) and its trianion, which marks a milestone in this field, given that several phosphino triphenolate complexes and cluster compounds have been prepared thereafter .…”
Section: Introductionmentioning
confidence: 99%
“…There is intense current interest in the preparation and isolation of stable phosphoniumyl radical cations (Bullock et al, 2013;Boeré et al, 2008;Sasaki et al, 2002Sasaki et al, , 2004Sasaki et al, , 2006Sasaki & Yoshifuji, 2007;Chalier et al, 1996). Exhaustive studies have shown that this can be achieved only when very bulky substituents are employed, and thus far all the successful examples use bulky aryl groups.…”
Section: Introductionmentioning
confidence: 99%
“…Acidic hydrolysis of (1) produces yellow colored tris(2-formylphenyl)stibine (3). When stibine (3) was reduced with NaBH 4 in ethanol water mixture, an unexpected oxastibol (4) [16] was obtained from the corresponding formylphosphine.…”
Section: Resultsmentioning
confidence: 99%